Reconfigurable intelligent surface assisted downlink INOMA system - Kumar M.H.; Sharma S.; Thottappan M.; Deka K. (My University, 2025)
Nonorthogonal multiple access (NOMA) and reconfigurable intelligent surface (RIS) methods are explored to enhance spectral and energy efficiency of a wireless network. In this article, we have proposed a downlink RIS-assisted index modulation NOMA for next-generation wireless systems, and it is referred to as R-INOMA. In the proposed R-INOMA system, a base station transmits information through RIS to three users, the first user is assigned in the spatial domain and the remaining two users are multiplexed using power domain NOMA. We provide an analytical analysis of bit error probability (BEP) for the proposed R-INOMA system. Impact of number of surfaces, transmit antennas, modulation order, diversity order, and imperfect channel estimation is analyzed for the R-INOMA. Simulation results show that the proposed R-INOMA achieved better BEP and sum-rate over existing NOMA techniques. In the R-INOMA, doubling of the reflecting surfaces provides a 4 dB gain for a fixed error probability, and the sum-rate improves as the number of transmitting antennas and reflecting surfaces increases. © 2022 John Wiley & Sons, Ltd.